Phase separation in mitochondrial fate and mitochondrial diseases - Qingyi Chen; Sanqi An; Chuanlong Wang; Yanshuang Zhou; Xingguo Liu; Wenkai Ren (Proceedings of the National Academy of Sciences, 2025)
Mitochondria are central metabolic organelles that control cell fate and the development of mitochondrial diseases. Traditionally, phase separation directly regulates cell functions by driving RNA, proteins, or other molecules to concentrate into lipid droplets. Recent studies show that phase separation regulates cell functions and diseases through the regulation of subcellular organelles, particularly mitochondria. In fact, phase separation is involved in various mitochondrial activities including nucleoid assembly, autophagy, and mitochondria-related inflammation. Here, we outline the key mechanisms through which phase separation influences mitochondrial activities and the development of mitochondrial diseases. Insights into how phase separation regulates mitochondrial activities and diseases will help us develop interventions for related diseases.